2022
DOI: 10.3390/rs14163971
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Satellite Soil Moisture Datasets for Drought Monitoring in Australia and the South-West Pacific

Abstract: Soil moisture (SM) is critical in monitoring the time-lagged impacts of agrometeorological drought. In Australia and several south-west Pacific Small Island Developing States (SIDS), there are a limited number of in situ SM stations that can adequately assess soil-water availability in a near-real-time context. Satellite SM datasets provide a viable alternative for SM monitoring and agrometeorological drought provision in these regions. In this study, we investigated the performance of Soil Moisture Active Pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…A comprehensive analysis of the SWCEM satellite precipitation data performed over Australia showed that blended satellite-gauge products had higher correlations and smaller errors than gauge analysis [48][49][50][51][52][53]. Similarly, earlier studies demonstrated the usefulness of satellite precipitation data not only for Australia but also for countries in the Pacific region [54,55], which means that the SWCEM data as well as the developed in this study flood risk assessment methodology could potentially be used in other countries in the Asia-Pacific region.…”
Section: Flood Hazard Indicators and Data Collectionsupporting
confidence: 59%
“…A comprehensive analysis of the SWCEM satellite precipitation data performed over Australia showed that blended satellite-gauge products had higher correlations and smaller errors than gauge analysis [48][49][50][51][52][53]. Similarly, earlier studies demonstrated the usefulness of satellite precipitation data not only for Australia but also for countries in the Pacific region [54,55], which means that the SWCEM data as well as the developed in this study flood risk assessment methodology could potentially be used in other countries in the Asia-Pacific region.…”
Section: Flood Hazard Indicators and Data Collectionsupporting
confidence: 59%
“…This dataset provides SM with a temporal resolution of 1 h and a horizontal resolution of 0.1 • , measured in volumetric water content (m 3 /m 3 ). The SM data are divided into four layers based on depth: 0-7 cm, 7-28 cm, 28-100 cm, and 100-289 cm [45,46]. For this study, SM data from the 0-7 cm soil layer at 12:00 UTC were selected for analysis.…”
Section: Era5-landmentioning
confidence: 99%
“…Research based on the vegetation index cannot fully desc damage caused by high temperatures, and there is a relatively obvious lag. R based on hyperspectral remote sensing has many inconveniences in data acquisit complex physical model construction [41][42][43][44][45]. Therefore, this study uses remote data with high temporal resolutions, including MODIS surface reflection data and land surface temperature products to extract vegetation temperature-sensitive ban combines LST to construct a remote sensing index, LSHDI (land surface heat dam dex), which can more comprehensively reflect the growth environment of vegetati study also analyzes the trend in the LSHDI to obtain the temporal and spatial cha the study area.…”
Section: Study Areamentioning
confidence: 99%